PENGEMBANGAN LKS BERBASIS DIGITAL PADA MATA PELAJARAN IPA KELAS VII SMP - ' Monica Pratiwi, Zuliarni (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2020)
In this research and development (Researh and Development) based on the Borg and Gall model. The purpose of research on developing digital-based student worksheet (LKS) media products that has been produced has gone through validation procedures and product practicality which is shown to seventh grade students of SMP. The process of the validation sheet and the practicality sheet was prepared by previous researchers with stages in accordance with the rules of assessment. Based on the results of the feasibility review of the products that have been developed from 2 lecturers of the Education Technology Study Program and 1 teacher of Natural Sciences (IPA) SMPN 22 Padang, from the assessment of the overall media aspect of the two validators of the score acquisition it can be concluded that the media has the criterion is classified as